2002
DOI: 10.1002/1521-4141(200206)32:6<1621::aid-immu1621>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific T cell suppression by human CD4+CD25+ regulatory T cells

Abstract: Anergic/suppressive CD4+CD25+ T cells have been proposed to play an important role in the maintenance of peripheral tolerance. Here we demonstrate that in humans these cells suppress proliferation to self antigens, but also to dietary and foreign antigens. The suppressive CD4+CD25+ T cells display a broad usage of the T cell receptor Vβ repertoire,suggesting that they recognize a wide variety of antigens. They reside in the primed/memory CD4+CD45RO+CD45RBlow subset and have short telomeres, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
180
2
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(198 citation statements)
references
References 35 publications
9
180
2
5
Order By: Relevance
“…The reduced downregulatory effect in patientderived CD4 + CD25 high T cells was detectable in the presence of unaltered CD4 + CD25 -T eff proliferation and concomitant IFN-c production, as previously described in several studies [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The reduced downregulatory effect in patientderived CD4 + CD25 high T cells was detectable in the presence of unaltered CD4 + CD25 -T eff proliferation and concomitant IFN-c production, as previously described in several studies [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 77%
“…The murine counter- part of this T cell subset has an established role in the prevention of organ-specific autoimmune disease, including experimental allergic encephalomyelitis [5,26]. A similar subpopulation of CD4 + CD25 high T cells is present in human peripheral blood and lymphoid organs [6][7][8][9][10][11][12][13]. From a few recent studies, it appears that T reg numbers are reduced or their function is impaired in patients with various autoimmune disorders [17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4a). Collectively, these data demonstrated that Treg expanded in vitro with two or three cycles of xenoantigen-but not polyclonal-stimulation possessed the phenotypic characteristic of effector Treg, an important indicator for enhanced Treg function in immune suppression (Taams et al 2002;Dieckmann et al 2001;Baecher-Allan et al 2006). Furthermore, the increased level of Treg effector cytokine IL-10 gene expression by xenoantigen-stimulated Treg suggested that Xn-Treg may acquire potent suppressive activity in xenogeneic responses both in vitro and in vivo via IL-10-involved mechanisms (Sun et al 2010a, b;Yi et al 2012).…”
Section: High Numbers Of Human Treg Are Obtained After Expansion Withmentioning
confidence: 84%